Study on "Four-Property Relationship" and Effective Thickness Lower Limit of Chang4+5 Reservoir in Zhenbei Area - Fu, Bolin; Qu, Le; Shen, Yang (Scientific Journal of Technology, 2026)
Zhenbei Area is located on the southwestern margin of the Ordos Basin, north of Zhenyuan County. The Yanchang Formation is a key horizon for oil and gas exploration and development in this region. Although certain exploration achievements have been made in Chang 8, Chang 7 and Chang 3 members of the Yanchang Formation in Zhenbei Area, the Chang4+5 member has multiple oil-producing wells and great exploration potential. Controlled by different sediment sources, the Chang4+5 reservoir in Zhenbei Area is lithologically different from that in adjacent eastern blocks, and can be subdivided into Chang4+5₂ and Chang4+5₁ sub-members vertically. As a typical low-permeability reservoir with complex oil-water distribution, low resistivity and low oil saturation, it is difficult to identify oil and water layers by conventional methods. Based on core data, grain size analysis, physical property parameters, logging and production performance data, this study systematically analyzed the four-property relationship (lithology, physical property, electrical property and oil-bearing property) of the Chang4+5 reservoir in Zhenbei Area, established logging interpretation models, and clarified the lower limits of physical property, oil-bearing property, electrical property and effective thickness. The results show that the Chang4+5 reservoir is dominated by fine sandstone and extra-fine sandstone, with low porosity and extra-low permeability; obvious electrical differences exist between eastern and western parts of the study area; the lower limits of physical property are porosity >9% and permeability >0.1 mD, and the lower limit of effective thickness is 0.4 m. This study provides a reliable basis for reservoir evaluation, fluid identification and reserve calculation of the Chang4+5 reservoir in Zhenbei Area.